Interpersonal communication of young married couples in maintaining their households - Rosita, Intan; Idrus , Nurul Ilmi; Abidin, Kurniati; Basir , Muhammad (Gema Wiralodra, 2024)
As social beings who cannot live alone, humans need other people to fulfill their needs to interact where they will communicate, convey their will, feelings and ideas. In everyday life, no matter where it is, humans must always interact and communicate with certain people who come from groups, races, ethnicities or cultures, is a new experience that is always faced. the research method used in this research is qualitative, data collection techniques are interviews and documentation studies. The results showed that the form of communication of young couples in resolving household conflicts in Ajallase Village is a linear model, this linear model is a communication process that is said to be sufficient if one person sends a message and another person receives the message. The obstacles faced by young couples in Ajallasse Village, Cenrana District in overcoming household conflicts are egoism, low economic factors. The solution of young couples in resolving household conflicts in Ajallasse Village, Cenrana Subdistrict, Bone Regency is to try to build deeper (intimate) relationships with their respective partners, always open to their partners (communicate)